Die plek en taak van ’n onderwysvereniging* - Postma, W. (Koers, 1983)
With the increase in scientific knowledge and as a result o f the stringent demands of modern society refined and specialized professional educators (teachers) have had to assume their own unique task, place and responsibility. Teachers, who have a calling and who are carriers o f authority together with parents, have their own professional interests that have to be looked after. With a view to rendering service to teachers various teachers’ societies have come into being (teachers within an organized relationship). These teachers' associations fill a specific, unique, place within the education system, and on the basis of this position teachers' associations have specific tasks or functions. The tasks of the teachers’ association range from professional rendering of service to a wider participation in the shaping of culture and the dissemination of culture. To what extent teachers ’ associations assume a characteristic role in South Africa and will still assume in the future is shown in a survey in this article. The task (function[s]) of teachers' associations is also briefly outlined and made applicable to South Africa an circumstances.